Diastereoselective self-assembly of a triple-stranded europium helicate with light modulated chiroptical properties. Issue 13 (12th March 2021) - Zhang, Zhihui; Zhou, Yanyan; Gao, Ting; Yan, Pengfei; Zou, Xiaoyan; Li, Hongfeng
Abstract : The Eu 3+ helicate that combines supramolecular chirality, luminescence and photochromic properties shows light-responsive chiroptical (ECD and CPL) switching properties upon alternating UV and visible light irradiation. Abstract : Chiroptical photoswitches are of increasing interest for their potential in advanced information technologies. Herein, an achiral bis-β-diketonate ligand ( o -L ) with a photoresponsive diarylethene moiety as a linker was designed, which co-assembled with Eu 3+ ions and R - and S -bis(diphenylphosphoryl)-1, 10-binaphthyl ( R / S -BINAPO) as chiral ancillaries to form dinuclear triple-stranded helicates, [Eu2 ( o -L )3 ( R / S -BINAPO)2 ]. The helicates in the enantiopure form were confirmed by 1 H, 19 F, 31 P NMR and DOSY NMR analyses. Furthermore, the mirror-image CD and CPL spectra also demonstrate the existence of stable ground- and excited-state chiralities in solution. When exposed to alternate ultraviolet and visible light, the helicates showed reversible color variations from colorless to purple, followed by the presence of light-triggered quadruple optical and chiroptical outputs, named CD, PL, CPL and g lum switches. With these light-modulated optical outputs, the possibility for the fabrication of IMPLICATION and INHIBIT logic gates was discussed.